DprE1, a new taxonomic marker in mycobacteria. Issue 1 (12th September 2013) - Incandela, Maria Loreto; Perrin, Elena; Fondi, Marco; de, Ana Luisa; Mori, Giorgia; Moiana, Alessia; Gramegna, Maurizio; Fani, Renato; Riccardi, Giovanna; Pasca, Maria Rosalia
Abstract Among the species of the Mycobacterium genus, more than 50 have been recognized as human pathogens. In spite of the different diseases caused by mycobacteria, the interspecies genetic similarity ranges from 94% to 100%, and for some species, this value is higher than in other bacteria. Consequently, it is important to understand the relationships existing among mycobacterial species. In this context, the possibility to use Mycobacterium tuberculosis dprE1 gene as new phylogenetic/taxonomic marker has been explored. The dprE1 gene codes for the target of benzothiazinones, belonging to a very promising class of antitubercular drugs. Mutations in cysteine 387 of DprE1 are responsible for benzothiazinone resistance. The DprE1 tree, obtained with 73 amino acid sequences of mycobacterial species, revealed that concerning the benzothiazinone sensitivity/resistance, it is possible to discriminate two clusters. To validate it, a concatamer obtained from the amino acid sequences of nine mycobacterial housekeeping genes was performed. The concatamer revealed that there is no separation between the benzothiazinone‐susceptible and benzothiazinone‐resistant species; consequently, this parameter is not linked to the phylogeny. DprE1 tree might represent a good taxonomic marker for the assignment of a mycobacterial isolate to a species. Moreover, the concatamer represents a good reference phylogeny for the Mycobacterium genus.